IT01-T Appennini: ecosistemi d'alta quota - Stanisci, Angela; Cutini, Maurizio; Petriccione, Bruno; Rossi, Graziano; Calderaro, Chiara; Carranza, Maria Laura; De Cecco, Valter; Frate, Ludovico; Giancola, Carmen; Di Martino, Luciano; Di Musciano, Michele; Tognetti, Roberto; et al. (Zenodo, 2021)
The macro-site includes the following research sites along the Apennine mountain range: LTER_EU_IT_022 – Central and Southern Apennine: Majella-Matese LTER_EU_IT_025 – Central Apennine: Velino-Duchessa LTER_EU_IT_024 – Central Apennine: Gran Sasso LTER_EU_IT_023 – Northern Apennine It consists of "orographic islands" with high elevation vegetation in central Mediterranean basin, along the Apennines mountain range. It includes permanent plots where long term ecological monitoring is carried out. They are distributed in the three geographical sectors of Apennines: Northern Apennines: the permanent plots are placed between the timberline zone and the alpine belt (1800-2120 m); they are included into the worldwide network of GLORIA project (GLObal Research Initiative in Alpine ecosystems). Other permanent plots are devoted to the monitoring of snow cover and of the populations of vascular plants at extinction risk. Central Apennines: the oldest permanent plots are located at Gran Sasso d'Italia (since 1986) and at Mt.Velino (since 1993), in alpine tundra and primary grasslands. Since 2001 the ecological monitoring of the alpine belt in Majella national Park started, according to the standardized methodological protocol of the worldwide network GLORIA; the plots are placed along an elevation gradient between dwarf shrublands and tundra vegetation (2400-2730 m). Moreover, the wood anatomy and dendrochronology of beech and mountain pine are being studied. Since 2005, in M.ts Velino and Duchessa other permanent plots are monitored along two separate elevation transects on the south-western slopes of M.te Morrone (1100-2141 m a.s.l., Montagna della Duchessa, Lazio) and M.te Sevice-M.te Velino (1100-2487m a.s.l., Velino massif, Abruzzo), including grasslands, open beech forest, timberline and high elevation vegetation. Southern Apennines: since 2007 other permanent plots are monitored in Matese mountains (1800-2000 m a.s.l.), included into the worldwide network GLORIA, and characterised by ridges grasslands. The research ...